Pengaruh Lobe Of Money dan Machiavellian Terhadap Persepsi Mahasiswa Akuntansi - Wunu, Stevania; Banda, Falentina Lucia; Thalib, Sabra B Wahab (Jurnal Riset Ilmu Akuntansi, 2021)
This study aims to determine first, how the variable Love of money affects the Ethical Perceptions of Accounting Students at the University of Flores. Second, to determine the influence of Machiavellian on the Ethical Perceptions of Accounting Students at the University of Flores. This research was conducted at the University of Flores Educational Institute, with a total population of 532 accounting students. Samples taken were 56 respondents. This study uses a quantitative approach. The method used in this research is to distribute questionnaires to students who have programmed business and professional ethics courses. In this research, several tests were used including instrument test, classical assumption test and hypothesis test. The results of this study indicate that (1) Love of money has a negative and significant effect on students' ethical perceptions. (2) Machiavellian also has a negative and significant effect on ethical perceptions of accounting students. (3) Love of money and Machiavellian together have a negative and significant effect. significant towards ethical perceptions.